Pengembangan Lkpd Berbasis Pembelajaran Berdiferensiasi Untuk Meningkatkan Kemampuan Berpikir Kritis Matematis - Natalia Salim, Aisyah; Risnanosanti, Risnanosanti; Jumri, Rahmat; Asmara, Adi; Ariani, Nyayu Masyita (Jurnal Pendidikan Matematika : Judika Education, 2026)
This research aims to improve students' mathematical critical thinking skills through differential learning. This research is an R&D (Research and developmet) development research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research is limited to Implementation only. This study involved 29 students and 1 mathematics teacher in class VII of SMP Negeri 7 Bengkulu City. The research instruments are in the form of validation sheets and questionnaires on the practicality of students and teachers. The results of the study showed that the LKPD developed obtained a validity Result Level of 84.48% with a valid category. The results of the practicality test obtained a percentage of 87.5% of students with the very practical category. Meanwhile, the results of the practicality test obtained a percentage of 87.8% from teachers in the very practical category. The results of this study show that the development of LKPD based on differentiated learning is feasible for use in learning.   Keywords: LKPD, Differentiated Learning, Mathematical Critical Thinking, ADDIE Model